2016
DOI: 10.1016/j.fsi.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increasing dietary levels of soy protein concentrate (SPC) on the immune responses and disease resistance (furunculosis) of vaccinated and non-vaccinated Atlantic salmon ( Salmo salar L.) parr

Abstract: (2016) The effects of increasing dietary levels of soy protein concentrate (SPC) on the immune responses and disease resistance (furunculosis) of vaccinated and non-vaccinated Atlantic salmon (Salmo salar L.) parr, Fish and Shellfish Immunology, 59, pp. 83-94.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…There are few studies in the literature were Atlantic salmon antibody responses have been analyzed as a function of dietary FAs. Metochis et al (2016) [89] tested total IgM in Atlantic salmon vaccinated against A . salmonicida which received different amounts of soy protein.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature were Atlantic salmon antibody responses have been analyzed as a function of dietary FAs. Metochis et al (2016) [89] tested total IgM in Atlantic salmon vaccinated against A . salmonicida which received different amounts of soy protein.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that soybean meal and isolated soy protein could replace 27.3% of dietary fishmeal without negatively affecting the growth performance in juvenile silvery-black porgy; however, a higher dietary soybean content induced signs of hyperlipidemia and anemia signs 4 . Similarly, several adverse effects on growth performance 5 , digestibility of nutrients 6 , feed efficiency 7 , immune responses 8 and intestinal health 2 were observed. Certain indigestible components (non-starch polysaccharides) 9 , and some anti-nutritional factors and low concentrations of lysine, methionine and threonine were considered restricting the use of soybean in aquafeeds 10 .…”
Section: Introductionmentioning
confidence: 97%
“…For instance, compared to fishmeal, the dietary inclusion of meat and bone meal significantly modulated gastrointestinal tract microbiota in the gilthead sea bream Sparus aurata juveniles, there was a marked increase in the number of individuals of Vibrio, Bacillus and Mycobacterium, whereas the numbers of Corynebacterium decreased (Moutinho et al, ). Considering the associations between dietary soybean meal and gut microbiota, and gut microbiota and intestinal health (Gatlin et al, ; Metochis et al, ; Miao et al, ), it is necessary to trace the changes in the gut microbiota caused by diets, which can ultimately affect host physiology (Bashiardes, Godneva, Elinav, & Segal, ). However, little is known about the way in, and the extent to, which responses may happen to gut microbiota when fish is fed with different protein sources.…”
Section: Introductionmentioning
confidence: 99%